Incidental Findings of Duodenal-Type Follicular Lymphoma by Endoscopic Screening: A Case Report - Herman Saputra; Ni Putu Sriwidyani; Putu Erika Paskarani; Silvia Khosasi (http://dharmais.co.id/, 2023)
Introduction: Follicular Lymphoma (FL) is a B-cell neoplasm arising from the germinal center. Gastrointestinal FL is a rare case, accounting for less than 4% of all primary lymphoma of the gastrointestinal tract. Duodenal-type Follicular Lymphoma (DTFL) was included in an entity of primary intestinal FL. However, in the 2017 World Health Organization (WHO) Classification, this entity was included in a specific variant called DTFL. In this article, we report a case of DTFL in a 56-year-old man which was incidentally found during upper gastrointestinal endoscopy Case Presentation: : We report a case of incidentally found DTFL in a 56-year-old man during an endoscopy. The endoscopic finding showed a small, hypertrophic, or nodular lesion on part two duodenum. Microscopic evaluation of duodenal mucosa consists of proliferative atypical lymphoid cells arranged in follicular architecture. The lesion was confined to the lamina propria. The atypical lymphoid cells were dominated by monotonous centrocyte-like cells, small-sized, with scant cytoplasm, and cleaved nuclei. There were some scattered larger centroblast-like cells with multiple nucleoli. No mantle zone and tingible body macrophage were found. The immunohistochemical evaluation showed positivity for CD 20, CD 10, Bcl-6, and Bcl-2 in the follicular structure. CD 21 was dominantly stained at the periphery of the follicular structure, and Ki-67 was low. Conclusions: According to clinical data, endoscopic findings, and histopathological and immunohistochemical findings, the patient was diagnosed with DTFL.